EFFECT OF INVERTED INTERNAL LIMITING MEMBRANE FLAP ON CLOSURE RATE, POSTOPERATIVE VISUAL ACUITY, AND RESTORATION OF OUTER RETINAL LAYERS IN PRIMARY IDIOPATHIC MACULAR HOLE SURGERY - Baumann, Carmen; Kaye, Stephen; Iannetta, Danilo; Sultan, Ziyaad; Dwivedi, Rahul; Pearce, Ian (Retina (Philadelphia, Pa.), 2020)
To investigate the role of an internal limiting membrane (ILM) flap in macular hole (MH) surgery on closure rate, visual acuity, and integrity of the outer retinal layers. Retrospective, nonrandomized interventional analysis in which 117 eyes of 117 patients were included who had undergone pars-plana vitrectomy (PPV) and gas tamponade for primary idiopathic MH >400 µm with either conventional ILM peeling or with inverted ILM flap technique at The Royal Liverpool University Hospital between January 2016 and April 2018. Main outcome measures were closure of MH, best-corrected visual acuity (BCVA) at 3, 6, and 12 months, and restoration of external limiting membrane and ellipsoid zone (EZ) using optical coherence tomography. Macular hole closure rate was significantly higher in patients with an ILM flap (67/68; 98.53%) than in those with conventional ILM peeling (43/49; 87.76%) (P = 0.02). Both groups showed significant improvements in their preoperative to postoperative BCVA at 3 months from 1.07 (0.43) logarithm of the minimum angle of resolution (logMAR) (20/235 Snellen) to 0.71 (0.34) logMAR (20/103 Snellen) (P <0.001), but there was no significant difference between the two groups (P = 0.45, P = 0.71). We found significant associations between postoperative BCVA and preoperative BCVA (P < 0.01) and the integrity of the EZ (P < 0.01). In 35 patients who had follow-up to 12 months, there was a significant improvement in BCVA between 3, 6, and 12 months from 0.73 (0.45) logMAR (20/107 Snellen) to 0.53 (0.24) logMAR (20/68 Snellen) and to 0.35 (0.18) logMAR (20/45 Snellen), respectively (P < 0.01). There was no significant difference at these time periods between the two groups (P = 0.62, P = 0.21, P = 0.31). The integrity of the EZ also improved significantly between 3, 6, and 12 months (P = 0.01), irrespective of the presence of an ILM flap (P = 0.58), but with a trend toward delay in restoration in those patients with an ILM flap. The improvement in BCVA at 12 months, taking into account the age of the patient, size and duration of the MH, presence of an ILM flap, and preoperative BCVA was dependent on the state of the EZ (P = 0.01). In patients undergoing primary pars-plana vitrectomy for MH >400 µm, the presence of an inverted ILM flap was associated with a significantly higher closure rate than a conventional ILM peeling. Best-corrected visual acuity showed a strong correlation with the integrity of the EZ and both improved significantly between 3, 6, and 12 months, irrespective of the presence of an ILM flap.